Using Acer platanoides annual rings to monitor the amount of heavy metals accumulated in air - Turkyilmaz, Aydin; Sevik, Hakan; Isinkaralar, Kaan; Cetin, Mehmet (Springer Science and Business Media LLC, 2018)
Annual rings are good indicators for determining the increase in the amount of heavy metals in the atmosphere from past to the present. Air pollution has rapidly increased in Ankara over the past 20 years. In particular, there is a serious increase in the concentration of heavy metals that adversely affect human health. In this study, the accumulation of Al, Zn, Cu, Co, Fe, Mn, Cr, Cd, Na, Ca, Ba, P, Mg, As, and B on Acer platanoides rings has been determined using the GBC Integra XL-SDS-270 ICP-OES instrument. Based on our experimental findings, we determined that the concentration of heavy metals accumulated on the rings over the past 20 years varied and that there was a significant correlation between heavy metal concentration in air and heavy metal accumulation on trees. The main reasons for this increase were an increase in the amount of exhaust emission gases and most importantly the transport of heavy metals by the prevailing winds from heavy industrial plants established after 1990 in Ankara. As a result, when the values were examined, we found that except for Na, all the elements, which showed differences at statistically significant levels, were in considerably high quantities in the bark. On average, the values obtained for bark were 6 times higher than those obtained for wood. In terms of elements that showed statistically significant level of differences, this difference was the lowest in P (1.61 times higher), Mg (2.52 times higher), and B (3.94 times higher) and the highest in Mn (23.87 times higher), Al (22.0 times higher), and Fe (14.27 times higher). In the case of Na, we found that the value obtained for wood was 1.64 times higher than that obtained for bark.
Keywords: Air Pollutants; Turkey; Atmosphere; Acer; Trees; Air Pollution; Metals, Heavy; Humans; Environmental Monitoring; Vehicle Emissions; 15. Life on land; 13. Climate action; 11. Sustainability